Analysis of the Students' Digital Literacy Skills through Blended Learning at Madrasah Ibtidaiyah in the Post Covid-19 Pandemic - Idah Faridah Laily; Misbah Binasdevi (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThe purpose of this study was to analyze how blended learning could enhance the students’ digital literacy skills. The mix of methodologies employed in this study was based on the sequential transformative strategy paradigm. Participants in this study were 7 teachers and 80 students from three Madrasah Ibtidaiyah located in Cirebon City, West Java, Indonesia. The data for this study were gathered using both qualitative and quantitative methods, including interviews, observations, triangulation, documentation, and questionnaires. Then, both qualitative and quantitative techniques were used to analyze the data. The findings revealed that the teachers had utilized blended learning stages according to the six existing criteria. However, not all schools had implemented the same blended learning concept. According to the quantitative data, 74.1% of students said their teachers had successfully used blended learning on average. Additionally, a simple linear regression calculation with a significant value of 0.000<0.05 was used to support the hypothesis that the utilization of blended learning affected the students' digital literacy skills.Keywords: digital literacy, blended learning, madrasah ibtidaiyah students.AbstrakPenelitian ini bertujuan untuk menganalisis bagaimana blended learning dapat meningkatkan kemampuan literasi digital siswa. Perpaduan metodologi yang digunakan dalam penelitian ini didasarkan pada paradigma strategi transformatif sekuensial. Partisipan dalam penelitian ini adalah 7 guru dan 80 siswa dari 3 Madrasah Ibtidaiyah yang ada di Kota Cirebon, Jawa Barat, Indonesia. Data penelitian ini dikumpulkan dengan menggunakan metode kualitatif dan kuantitatif, meliputi wawancara, observasi, triangulasi, dokumentasi, dan angket. Kemudian, teknik kualitatif dan kuantitatif digunakan untuk menganalisis data. Hasil penelitian mengungkapkan bahwa guru Madrasah Ibtidaiyah di Kota Cirebon, Jawa Barat telah memanfaatkan tahapan blended learning sesuai dengan 6 (enam) kriteria yang ada. Namun demikian, tidak semua sekolah menerapkan konsep blended learning yang sama. Menurut data kuantitatif, 74,1% siswa mengatakan bahwa guru mereka telah berhasil menggunakan blended learning. Selain itu, perhitungan regresi linier sederhana dengan nilai signifikansi 0,000<0,05 digunakan untuk mendukung hipotesis bahwa pemanfaatan blended learning berpengaruh terhadap kemampuan literasi digital siswa.Kata kunci: literasi digital, blended learning, siswa madrasah ibtidaiyah.